Ectopic and Utopic Reproduction: He, She and It. - Deery, June (Utopian Studies, 1994)
Discusses the elements of cyborgs and virtual reality as depicted in the book `He, She and It,' by Marge Piercy. Impact of technology on conception, gestation and delivery; Definition of humans; Interplay of fiction and reality in utopian literature.